Did The Number of Capital, Number of Workers and Age Affect The Performance of BUMDes? - Sinarwati, Ni Kadek; Telagawathi, Sayang; Adiputra, Pradana; Astawa, Banu; Marhaeni, AAIN (Jurnal Ekonomi Kuantitatif Terapan; 2023: Vol. 16, No. 2, Agustus 2023 (pp.187-360)DO - 10.24843/JEKT.2023.v16.i02.p08, 2023)
Previous research found that BUMDes in Bali Province had good performance even in the midst of the Covid-19 pandemic. Whether factor affects the performance of BUMDes is important to analysis. Did the Number of Capital, number of workers, and age affect the performance of BUMDes?.  This study aims to analyze the effect of the Number of Capital, number of workers, and age on the performance of BUMDes. Data collection using documentation methods. The data analysis technique was multiple regression. The population were all BUMDes in Bali Province, the sample was determined by purposive method with the criteria researchers can find the research data needed in this study.  The results showed that the number of capital had a negative but not significant effect on performance, the number of workers and age had a positive but not significant effect on the performance of BUMDes.